THE APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES ON SOCIAL STUDIES SUBJECTS IN GRADE IV OF ELEMENTARY SCHOOL II TANJUNGSARI - Rukmini, Piyantina; Setiawardani, Wawan; Widiyanti, Widiyanti (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This research was conducted using the classroom action research (CAR) method. The progress in learning and storytelling skills is still below the Minimum Completeness Criteria and success indicators. The study included 142 students from SDN 2 Tanjungsari, ranging from grade I to grade VI. 36 sixth-grade students were part of the sample, with an equal number of males and females. The researcher collected data using tests and observations. The research instruments were observation sheets and test sheets. The analysis techniques used were qualitative and quantitative analysis. The results of this study showed that the students' learning outcomes in cycle I had a mastery level of 27.78%. In cycle II, there was an improvement in student learning outcomes with a mastery level of 52.78%. In cycle III, the mastery level reached 83.33%. This indicates that the students' learning outcomes had met the applied mastery criteria of 80%. The study also observed students' learning activities. In cycle I, the students' activities scored 19 with a percentage of 1.58%, which was still categorized as poor. In cycle II, there was an improvement in students' learning activities with a score of 27 and a percentage of 2.25%, categorized as moderate. In cycle III, students' learning activities had a score of 41 with a percentage of 3.42%, which was categorized as good. Research using Problem-Based Learning can enhance learning outcomes and student engagement in Social Studies for fourth-grade students at SDN 2 Tanjungsari in Indramayu District.